Perempuan dan Politik pada Rekrutmen Politik Calon Legislatif Perempuan di Partai Keadilan Sejahtera - NZ, Nurrahmi; Sitepu, P Anthonius (Politeia: Jurnal Ilmu Politik, 2017)
This study describes the political recruitment of women legislative candidates in the Prosperous Justice Party in the 2004 elections. When viewed from the number of administrators at the regional level, the number of PKS female cadres is 1,010 while the male cadre is 1,240, of which it can be seen that women in PKS it has a high level of participation but this has not yet determined that PKS women are actively involved in party activities, one example can be seen from the number of PKS management offices in Medan City. The number of women involved in PKS does indicate the success of the cadre system that was created. And does this also indicate that the party has carried out the functions of political parties mainly associated with political recruitment. The DPD of the Prosperous Justice Party (PKS) is one of the political institutions that in its capacity to handle and become a forum in the political activities of the community, including the political problems of women who are part of the community. It is important for women to push for womens representation in the legislature. One of the starting points, womens equality in politics is an affirmative action according to Law Number 12 of 2003, article 65 paragraph 1 which states the importance of womens representation in politics especially after the reform order was implemented.